The Effect of Poster Media on Sanitation Practices for Manual Facial Care Tools at SMK Negeri 1 Pogalan - Husna, Aida Nur Shofiyatul Husna; M.A. Hanny Ferry Fernanda; Nia Kusstianti; Dindy Sinta Megasari (Jurnal Tata Rias, 2026)
Proper instrument sanitation practices are a critical skill in manual facial care. However, students’ compliance levels prior to the intervention remained low, indicating that visual aids are necessary to clearly convey sanitation procedures. The purpose of this study was to determine the feasibility of using a poster as a medium for instrument sanitation SOPs, students’ psychomotor learning outcomes, and how this impacts the instrument sanitation behavior of 10th-grade Beauty Therapy students at SMK Negeri 1 Pogalan. The study involved 36 students using a quantitative, one-group, three-stage design (pretest, treatment, posttest). Observational data were analyzed using descriptive statistics and repeated-measures analysis of variance (ANOVA). The results showed that the poster and the observation instrument were “Highly Feasible” (89% and 93%), the average behavior score increased from 45.56 (pretest) to 90.33 (posttest), and the ANOVA test demonstrated a significant effect (F=288.916; Sig=0.000; p<0.05). The poster medium was proven to be appropriate and effective in significantly improving students’ equipment sanitation behavior; therefore, it is recommended that it be actively and continuously implemented in sanitation practice instruction. Keywords: Poster Media, Sanitation Practices, Sanitation of Equipment, Manual Facial Care.